PERLINDUNGAN ANAK PERSPEKTIF HUKUM ISLAM DAN PERUNDANG-UNDANG - nurlaila harun (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2018)
Abstract. Children are children, and not little adults. Thus, the treatment of children whether involved in criminal acts or those experiencing social problems must be addressed for the welfare of children. The need for children adoption within Indonesian Islamic community will also be increasingly important for those who need it, in order to obtain legal certainty in which can be obtained by a court decision including the decision of the Religious Court. The marriage law and religious justice law have regulated in detail about child care and guardianship which are compiled in a compilation of Islamic law. The Law on Religious Courts explicitly states that the Religious Courts are a court for Muslims regarding cases or matters that are in its authorities. Muslims in this case are not only adults but also children. Unfortunately, the issue of children protection is not referred explicitly in the authorities of the Religious Courts. However, to serve and to fulfill the legal needs of Muslims regarding to child care, the Religious Courts, at the request of someone who adopts a child based on Islamic law, may issue a decision on adoption in terms of the child concerned as a proof of completion of the will must be regulated in the Compilation of Islamic law of Religious Courts. Consequently, the rights and obligations of parents who have adopted children with Islamic law have special characteristics that are different from the rights and obligations of parents who have adopted children without Islamic law. Abstrak. Anak-anak adalah anak-anak, dan bukan orang dewasa kecil. Dengan demikian, perlakuan terhadap anak-anak apakah terlibat dalam tindakan kriminal atau mereka yang mengalami masalah sosial harus ditangani untuk kesejahteraan anak-anak. Kebutuhan adopsi anak dalam komunitas Islam Indonesia juga akan semakin penting bagi mereka yang membutuhkannya, untuk mendapatkan kepastian hukum yang dapat diperoleh melalui keputusan pengadilan termasuk keputusan Pengadilan Agama. Hukum perkawinan dan hukum keadilan agama telah mengatur secara rinci tentang pengasuhan anak dan perwalian yang disusun dalam kompilasi hukum Islam. Undang-Undang tentang Pengadilan Agama secara eksplisit menyatakan bahwa Pengadilan Agama adalah pengadilan bagi umat Islam tentang kasus atau hal-hal yang ada dalam otoritasnya. Muslim dalam hal ini tidak hanya orang dewasa tetapi juga anak-anak. Sayangnya, masalah perlindungan anak tidak dirujuk secara eksplisit dalam otoritas Pengadilan Agama. Namun, untuk melayani dan memenuhi kebutuhan hukum umat Islam terkait perawatan anak, Pengadilan Agama, atas permintaan seseorang yang mengadopsi anak berdasarkan hukum Islam, dapat mengeluarkan keputusan tentang adopsi dalam hal anak yang bersangkutan sebagai bukti penyelesaian kehendak harus diatur dalam Kompilasi hukum Islam Pengadilan Agama. Akibatnya, hak dan kewajiban orang tua yang mengadopsi anak dengan hukum Islam memiliki karakteristik khusus yang berbeda dengan hak dan kewajiban orangtua yang mengadopsi anak tanpa hukum Islam.